Catalytic asymmetric conjugate addition of mercaptans to β-substituted-β-trifluoromethyl oxazolidinone enoates : access to chiral trifluoromethylated tertiary thioethers and thiols - Chen, Wenchao (2014)
The first asymmetric conjugate addition of mercaptans to β-substituted-β-trifluoromethyl oxazolidinone enoates has been developed. The opposite enantiomers of adducts, containing a trifluoromethylated hetero-quaternary stereogenic centers, could be obtained by utilizing two pseudo-enantiomeric Cinchona alkaloid-derived tertiary amine/squaramides as catalysts. Potassium dihydrogen phosphate was found to accelerate the reaction rate without compromising the enantioselective excess. A variety of chiral trifluoromethylated tertiary thioethers and thiols were readily prepared with excellent enantioselectivity.